Statistical and Bioinformatics Framework for Evaluating TERT Variants: Implications in T elomere Biology and Oncogenesis - Usha Adiga, Supriya P, Alfred J Augustine, Sampara Vasishta (South Eastern European Journal of Public Health, 2025)
Background: Telomerase reverse transcriptase [ TERT] is a catalytic subunit of the telomerase enzyme complex that maintains genomic stability by elongating telomeres. While TERT is silenced in most somatic cells, its dysregulation is implicated in cancers, telomere syndromes, and age-related diseases. Beyond telomere maintenance, TERT participates in chromatin remodeling and cellular signaling. Understanding the functional and disease-related implications of TERT variants is essential for therapeutic advancements. The study integrates statistical rigor and bioinformatics, emphasizing the application of computational models in genomics to explore TERT’s multifaceted roles in genomic stability and cancer. Methods: We analyzed 1510 TERT variants from the ENSEMBL database using computational tools, including SIFT, PolyPhen, and CADD, to predict pathogenicity. Variants were prioritized based on thresholds [ SIFT < 0.05, PolyPhen > 0.9, CADD > 20], and clustering algorithms [ K-Means, MCL, DBSCAN] were applied to group functionally related proteins. Gene Ontology [ GO] and KEGG pathway enrichment analyses were performed using g:Profiler and DAVID to elucidate biological roles. Disease associations were explored via ClinVar, COSMIC, and literature mining. Results: 266 prioritized variants showed high pathogenic potential based on functional scores. K-means clustering revealed three distinct groups, linking TERT to telomere maintenance, Wnt signaling, and DNA repair. Functional enrichment highlighted TERT’s involvement in telomerase RNA binding and telomere elongation. Disease association studies identified links to cancer [ e.g., hepatocellular carcinoma] and telomere syndromes [ e.g., dyskeratosis congenita]. Network metrics confirmed a cohesive protein interaction network, with a clustering coefficient of 0.828 and a PPI enrichment p-value of 0.000332. Conclusion: This comprehensive analysis underscores TERT’s multifaceted roles in cellular biology and its association with genomic stability and disease. By integrating clustering, enrichment, and disease association analyses, the study provides a robust framework for understanding TERT’s therapeutic potential in cancer and age-related disorders.